From health to university extention: cursinho popular do PET-medicina, a successful project in the Ribeirão Preto Medical School - Soriano, Leonardo Araujo; Diniz, Alex Luís Araujo; Baseio, Maria Clara; Paula, Jayter Silva de (Medicina (Ribeirao Preto), 2016)
Design: Experience report. Relevance: Brazilian governments have promoted programs and actions to increase the access of students to the University. However, actions aimed to develop basic school levels has not grown accordingly, contributing to the maintanance of gaps in the students’ education and imposes obstacles to their admission in the universities. In this context, many free community preuniversity preparatory courses have been created as an alternative to overcome economic difficulties of people that cannot afford a private pre-university preparatory course. Medical students of the Program of Tutorial Education, from the Ribeirão Preto Medical School, University of São Paulo (PET-FMRP-USP), have managed such a free preparatory course called Cursinho Popular do PET-Medicina (CPM) since 2008. CPM has included, over the past seven years, more than 500 students, and 183 of them have been successfully accepted in public universities or in private ones with scholarships. Comments: Considering the university goals of teaching-research-extension, CPM has guaranteed benefits not only for poor students, but for everyone taking part of this project, including teachers and assistants, since they have improved skills related to inter-personal relationship and practiced citizenship